Inducibly decreased MITF levels do not affect proliferation and phenotype switching but reduce differentiation of melanoma cells - Vlčková, Kateřina; Vachtenheim, Jiri; Réda, Jiri; Horák, Pavel; Ondrušová, Lubica (Journal of cellular and molecular medicine, 2018)
Melanoma arises from neural crest-derived melanocytes which reside mostly in the skin in an adult organism. Epithelial-mesenchymal transition (EMT) is a tumorigenic programme through which cells acquire mesenchymal, more pro-oncogenic phenotype. The reversible phenotype switching is an event still not completely understood in melanoma. The EMT features and increased invasiveness are associated with lower levels of the pivotal lineage identity maintaining and melanoma-specific transcription factor MITF (microphthalmia-associated transcription factor), whereas increased proliferation is linked to higher MITF levels. However, the precise role of MITF in phenotype switching is still loosely characterized. To exclude the changes occurring upstream of MITF during MITF regulation in vivo, we employed a model whereby MITF expression was inducibly regulated by shRNA in melanoma cell lines. We found that the decrease in MITF caused only moderate attenuation of proliferation of the whole cell line population. Proliferation was decreased in five of 15 isolated clones, in three of them profoundly. Reduction in MITF levels alone did not generally produce EMT-like characteristics. The stem cell marker levels also did not change appreciably, only a sharp increase in SOX2 accompanied MITF down-regulation. Oppositely, the downstream differentiation markers and the MITF transcriptional targets melastatin and tyrosinase were profoundly decreased, as well as the downstream target livin. Surprisingly, after the MITF decline, invasiveness was not appreciably affected, independently of proliferation. The results suggest that low levels of MITF may still maintain relatively high proliferation and might reflect, rather than cause, the EMT-like changes occurring in melanoma.
Keywords: Neoplasm Invasiveness; messenger RNA; nádorové buněčné linie; Doxorubicin; Cell Movement; Cell Differentiation; melanoma; Melanoma; regulace genové exprese u nádorů; kontrolní body buněčného cyklu; differentiation; Cell Proliferation; Cell Line, Tumor; fenotyp; epitelo-mezenchymální tranzice; Epithelial-Mesenchymal Transition; Cell Cycle Checkpoints; Biomarkers, Tumor; Phenotype; Microphthalmia-Associated Transcription Factor; doxorubicin; nádorové biomarkery; melanom; RNA, Messenger; Humans; Gene Expression Regulation, Neoplastic; phenotype switching; pohyb buněk; invazivní růst nádoru; proliferace buněk; transkripční faktor spojený s mikroftalmií; buněčná diferenciace; Neoplastic Stem Cells; invasiveness; proliferation; nádorové kmenové buňky; MITF; lidé